PELATIHAN MANAJEMEN USAHA ANGKRINGAN GANG ZEPI DI KAMPUNG ECO GREEN PURWOSARI PERBALAN, SEMARANG - Kusumastuti, Aprillia Elly; Yuliana, Rahmi; Wahyuni, Asri Nur; Mursid, Ali; Hidayat, Dwi Suryanto (STIE Pelita Nusantara, 2025)
Eco Green Village, which promotes an environmentally friendly concept, is being developed within the creative economy and eco-based tourism sectors. The community in this area has the potential for micro-enterprises, including the angkringan (traditional food stall) business, a key component of Indonesian culinary culture. However, the challenges of changing consumer trends require businesses to adapt to the demands of cleanliness, comfort, and environmentally friendly concepts. Professional management training is a solution to improve business actors' skills in business planning, finance, marketing, and environmentally friendly practices. The goal is for angkringan businesses to become more than just a means of livelihood but also contribute to sustainable economic and environmental development. The training is expected to encourage orderly financial management, broader marketing through digital marketing, innovative product and service development, and a strong entrepreneurial mindset to increase the income and well-being of the surrounding community.Keywords: Eco green, angkringan business, digital marketing